Speech Act of the Main Character in “The Hobbit: An Unexpected Journey” - Mery Balango (Transbahasa, 2022)
Speech act is the utterance that speakers performs or speaker says in every speech. One of the benefits that can be learned on this study is help us to understand what hidden massage in every utterance. This research is aimed to explore the speech act in a fantasy film which is titled The Hobbit: An Unexpected Journey, The researcher pick this film as the object of research because this is a good film and the researcher finds some illocutionary acts. Moreover, the act of doing something as commonly known as Illocution, is a speech act that aimed at doing something (Parera, 1991:151). The concept of illocutionary act is expected to cover up the